2000
DOI: 10.1046/j.1537-2995.2000.40050535.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in cytoskeletal organization and tyrosine phosphorylation in platelet concentrates prepared by the buffy coat method

Abstract: These data indirectly suggest that the stress induced by the preparation method has an activating effect on platelet function that may imply a delayed platelet response to further stimuli. This effect may result in a deficient redistribution of signaling molecules within platelets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…35 Actin, a major component of the cytoskeleton, showed no change in its total amount in both studies, but revealed a shift toward more acidic isoforms during PLT storage. 36,37 [ 35 S]Methionine labeling, however, suggests that actin may be constitutively translated during PLT storage. Full-length b-actin mRNA was not well conserved in stored PLTs and showed a half-life of roughly 1.9 days (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…35 Actin, a major component of the cytoskeleton, showed no change in its total amount in both studies, but revealed a shift toward more acidic isoforms during PLT storage. 36,37 [ 35 S]Methionine labeling, however, suggests that actin may be constitutively translated during PLT storage. Full-length b-actin mRNA was not well conserved in stored PLTs and showed a half-life of roughly 1.9 days (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…It has been supposed that activation of PLTs might contribute to the development of the PSL 9 . Biochemical alterations in freshly processed PLTs in PCs resemble those induced by thrombin stimulation 10 . Therefore, inhibition of PLT activation during processing and storage might be an attractive strategy for protecting PLTs from getting activated, thus preserving PLT integrity in PCs during storage.…”
Section: Discussionmentioning
confidence: 99%
“…During the past several years, a number of groups have studied the morphologic and biochemical changes that occur during preparation and storage of PLTs and how these modifications may result in an impairment of PLT function [9][10][11] and even a delayed response to further stimuli. 12 Pathogen inactivation of plasma derivatives is being enforced by several health authorities. This policy is being extended to PLT concentrates (PCs) used for transfusion.…”
mentioning
confidence: 99%